Involving the private sector to improve the multiplication and marketing of high quality seed: the Direct Seed Marketing program in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2018)
PIM partnered with the Ethiopian Agricultural Transformation Agency (ATA) to test the pilot Direct Seed Marketing program. The study found that the program led to positive outcomes, and the ATA expanded it. In 2018, the program was used in 228 districts, involving 47 seed producers and benefiting 1.4 million farmers.